Women’s empowerment and the adoption of improved maize varieties: Evidence from Ethiopia, Kenya, and Tanzania - Seymour, Gregory; Doss, Cheryl; Marenya, Paswel Phiri; Meinzen-Dick, Ruth S.; Passarelli, Simone (2016)
Despite recent evidence that decisions about technology adoption often involve input from both men and women, the literature on technology adoption rarely considers gender and intrahousehold issues. In this paper, we use survey data from Ethiopia, Kenya, and Tanzania to investigate the influence of women’s empowerment on the adoption of improved maize varieties (IMVs). While our results are mixed as to whether or not women’s empowerment is positively correlated with higher rates of adoption, we find overwhelmingly that women’s empowerment is positively correlated with greater participation by women in decisions about the adoption of IMVs, the acquisition of credit for the purchase of IMVs, and the acquisition of extension services related to IMVs.